Female University Students Respond to Gender Violence through Dialogic Feminist Gatherings - Lidia Puigvert (RIMCIS, 2016)
Within the framework of the "Free_Teen_Desire" research project led by the University of Cambridge and funded by the programme Marie Curie Actions[i], a survey was conducted. Vignette-Test data for 127 female university students (ages 18-27 years) in Spain reveals that the wish to hook up with a violent young man significantly decreases after a gathering on the topic of the Mirage of Upward Mobility, a successful programme elaborated in Dialogic Feminism (Butler, Beck & Puigvert, 2003). In the pre-test,78.4%of the respondents stated that their female friends wouldliketo hook up with a violent man at a party, while this percentage decreased to 38.5% when they responded concerning themselves. After the pre-test, there was a one-hour gathering and debate. The subsequent post-test revealed that only 48.8%of the respondents stated that their female friends wouldliketo hook up with a violent man at a party, and 14.9% of the respondents made the same statement concerning themselves. The survey presented pictures of four men accompanied by a short explanation of their characters. The explanations of man 1 and man 3 included sentences that describe behaviours characterized as gender violence in previous international surveys (Banyard et al., 2005; Fisher, Cullen, & Turner, 1999; Gross et al., 2006; Kalof et al., 2001). The descriptions of man 2 and man 4 only included non-sexist behaviours. The data did not significantly change when we exchanged the pictures of man 2 and man 4 in the instrument with the pictures of the men with violent profiles and then administered the post-test. For different groups of respondents, the period between the pre-test and the gathering as well as between the gathering and the post-test were changed from fifteen minutes to one and two weeks. In all cases, we obtained similar results for the pre- and post-tests. However, additional research is required to demonstrate how long the effect of the gathering endures and to identify the processes that can increase or decrease the effect over time.